Microwave-assisted methylation of dihydroxybenzene derivatives with dimethyl carbonate. Issue 63 (17th June 2016) - Lui, Matthew Y.; Lokare, Kapil S.; Hemming, Ellen; Stanley, Jessica N. G.; Perosa, Alvise; Selva, Maurizio; Masters, Anthony F.; Maschmeyer, Thomas
Abstract : Dihydroxybenzene derivatives were methylated with dimethyl carbonate to generate useful synthetic intermediates for wide range of applications. Abstract : Using a focused microwave reactor, methylation with dimethyl carbonate (DMC) of 1, 2- and 1, 4-dihydroxybenzene derivatives, found in the product spectrum of lignin depolymerisation, leads to the respective aromatic bis-methyl ethers with excellent isolated yields. Stoichiometric as well as catalytic amounts of 1, 8-diazabicyclo[5.4.0]undec-7-ene (DBU) are effective for the bis-methylation of these dihydroxybenzenes at relatively mild temperatures (160–190 °C). Conversion of resorcinol (1, 3-dihydroxybenzene) under similar conditions leads to a mixture of 1, 3-dimethoxybenzene and methyl 2, 4-dimethoxybenzoate. The unusual reactivity of resorcinol's phenyl ring towards DMC can be explained by the synergic effect of its two strongly activating ortho / para directing groups.